2019
DOI: 10.3390/molecules24142519
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Characterization of Triterpene Saponins from Zornia brasiliensis by HPLC-ESI-MS/MS

Abstract: Zornia brasiliensis Vogel (Leguminosae) is a species popularly known in Brazil as “urinária”, “urinana”, and “carrapicho”, it is popularly used as a diuretic and in the treatment of venereal diseases. A specific methodology to obtain a saponin-enriched fraction and high-performance liquid chromatography coupled with diode array detection, ion trap mass spectrometry, and TOF-MS (HPLC-DAD-ESI-MS/MS) was applied for the analysis of triterpene saponins. The MS and MS/MS experiments were carried out by ionization i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…Saponin 37 (T R = 29.5 min) showed the same molecular ion as saponin 30 , [M-H] − ion at m / z 793 and exhibited MS 2 fragment ions at m / z 775 (water loss), m / z 731 (water and carbone dioxide losses), and m / z 613 (hexose and water losses). Therefore, this compound was assigned according to Nascimento et al as soyasaponin βe’ [ 33 ]. In addition, soyasaponin βg’ (compound 39 , T R = 30.34 min) was also identified in the same paper with a parent ion [M-H] − ion at m / z 763 and characteristic MS 2 fragment ions at m / z 719, 701, 613, 523, and 455.…”
Section: Resultsmentioning
confidence: 99%
“…Saponin 37 (T R = 29.5 min) showed the same molecular ion as saponin 30 , [M-H] − ion at m / z 793 and exhibited MS 2 fragment ions at m / z 775 (water loss), m / z 731 (water and carbone dioxide losses), and m / z 613 (hexose and water losses). Therefore, this compound was assigned according to Nascimento et al as soyasaponin βe’ [ 33 ]. In addition, soyasaponin βg’ (compound 39 , T R = 30.34 min) was also identified in the same paper with a parent ion [M-H] − ion at m / z 763 and characteristic MS 2 fragment ions at m / z 719, 701, 613, 523, and 455.…”
Section: Resultsmentioning
confidence: 99%
“…Identification of triterpene saponins by UHPLC‐UV‐MS/MS with CID in negative ion mode is a well‐established and widely employed technique 25,26,41 . Once known compounds are identified in the data set, database searches can be used as a guidance to discover the structure of new metabolites with modified core structures from a given class.…”
Section: Resultsmentioning
confidence: 99%
“…In this work we used MZmine 2 , which contains methods for all data processing stages, such as spectral filtering, peak detection, alignment, normalisation and identification 21 . Recent literature reports this tool for the structural determination of compounds from several metabolite classes such as flavonoids, 19,22 alkaloids, 17,23,24 and saponins 25,26 …”
Section: Introductionmentioning
confidence: 99%
“…Since natural products are one of the most important sources of new drugs, highly integrated interdisciplinary research methods have shown great power in drug discovery of natural products [2] . However, due to the similar structure and polarity of these compounds, they are difficult to separate with ordinary technology unless some special combined detection and separation technologies, such as HPLC‐ESIMS n , HPLC‐DAD‐MS, and HPLC‐PDA‐(HRMS)‐SPE‐NMR, which are wildly used to rapidly direct the isolation and identification of target compounds from crude extracts of medicinal plants [3–5] . Among them, by analyzing retention time ( t R ), UV spectrum data, fluorescence characteristics, extracted ion current (EIC) results, molecular weight and mass fragment behavior information based on HPLC/MS technology, it is easy to infer the corresponding components in a complex mixture [6–8] .…”
Section: Introductionmentioning
confidence: 99%